EFFECT OF MASH DIETARY FIBER ON PERFORMANCE AND CANNIBALISM IN LAYING HENS - Hartini, S.; Choct, M. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
An experiment was conducted to observe the effect of dietary fiber given in mash form onperformance and cannibalism mortality in laying hens. Three different diets: a wheat-based diet, a guargum diet (a wheat-based diet + 20 g/kg guar gum) and a lucerne meal diet (a wheat-based diet + 40 g/kglucerne meal) in mash form were offered for 12 weeks. The results showed that birds fed guar gum diethad the lowest intake (p<0.01), egg weight (p<0.05), body weight (p<0.05) and the lowest eggproduction (p<0.01) compared to those fed other diets. Diets did not have a significant effect (p>0.05)on feed to egg ratio and cannibalism mortality, but numerically the birds fed the guar gum diet had thehighest mortality (11.3%) and the lucerne diet had the lowest (6.9%). The lack of profound differenceswas probably due to the diets were given in mash form. In conclusion, diets containing high soluble NSPreduced the performance and increased the mortality due to cannibalism in laying hens. The use of mashform may have a potential in reducing the negative effect of soluble NSP on cannibalism.